ETNOPEDAGOGI DIGITAL: REAKTUALISASI KEARIFAN LOKAL KABUPATEN MERANGIN-JAMBI MELALUI GAME EDUKASI BERBASIS KEBUDAYAAN DI KELAS IV SD - Hopipah, Ria; Mutia Nurhamida; Yanti; Sindi; Hasri Agung Zulha; Mona Ariesta; Pebby Olla Yolanda; Mila Amelia; Ficri Amrullah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The massive wave of global modernization and digitalization threatens the existence of local wisdom values among the younger generation, including elementary school students in Merangin Regency, Jambi. Digital ethnopedagogy emerges as an alternative paradigm to integrate local cultural heritage with technological innovation. This study aims to develop, test the validity, practicality, and effectiveness of an educational game based on the